The impact of temperature on gaming productivity: evidence from online games - Xiaojia Bao; Qingliang Fan (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2018)
This paper studies the short-run impacts of temperature on human performance in the computer-mediated environment using server logs of a popular online game in China. Taking advantage of the quasi-experiment of winter central heating policy inChina, we distinguish the impacts of outdoor and indoor temperature and find that low temperatures below 5 ?C decrease game performance significantly. Non-experienced players suffered larger performance drop than experienced ones. Access to central heating attenuates negative impacts of low outdoor temperatures on gamers' performance. High temperatures above 21 ?C also lead to drops in game performance.We conclude that expanding the current central heating zone will bring an increase in human performance by approximately 4% in Shanghai and surrounding provinces in the winter. While often perceived as a leisure activity, online gaming requires intense engagement and the deployment of cognitive, social, and motor skills, which are also key skills for productive activities. Our results draw attention to potential damages of extreme temperature on human performance in the modern computer-mediated environment.
Keywords: Q54; J22; J24; D03; 330; Temperature; Human performance; Online game; Heating